2019
DOI: 10.1111/jace.16758
|View full text |Cite
|
Sign up to set email alerts
|

Selective preparation of Ag species on photoluminescence of Sm3+ in borosilicate glass via Ag+‐Na+ ion exchange

Abstract: Photoluminescence (PL) of rare earth ion‐doped glasses could be enhanced by diverse Ag species such as Ag+ ions, Ag+‐Ag+ pairs, Ag nano‐clusters (NCs), and Ag nanoparticles (NPs). Selective preparation of silver species in rare earth ion‐doped glasses is a crucial step to obtain the luminescence enhancement of rare earth ions caused by the different silver species. In this work, Ag+ ions and Ag NCs were selectively prepared in the Sm3+‐doped borosilicate glass via the Ag+‐Na+ ion exchange. The influence of AgN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…21 For example, in many previous researches [22][23][24] as well as in our recent work, 25 it was shown that the coinage ions introduced by the ion exchange processes could signicantly affect the optical properties of the glasses such as the refractive index, the optical density, the nearinfrared emission spectrum, or even chemically strengthen the glasses 26,27 as well as modify glass structure. 28 Through the ion exchange process, the Cu + and Cu 2+ ions, as well as Ag + ions, could be ejected into the surfaces of the glasses, 22,24,[29][30][31][32] then become neutral copper or/and silver atoms and grow into copper or/and silver nanoparticles (CuNPs or/and AgNPs). 24,29,32 Therefore, the ion exchange process between copper or/and silver cations and alkali cations to enhance the luminescence of Cr 3+ /RE 3+ co-doped has been studied in recent times.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…21 For example, in many previous researches [22][23][24] as well as in our recent work, 25 it was shown that the coinage ions introduced by the ion exchange processes could signicantly affect the optical properties of the glasses such as the refractive index, the optical density, the nearinfrared emission spectrum, or even chemically strengthen the glasses 26,27 as well as modify glass structure. 28 Through the ion exchange process, the Cu + and Cu 2+ ions, as well as Ag + ions, could be ejected into the surfaces of the glasses, 22,24,[29][30][31][32] then become neutral copper or/and silver atoms and grow into copper or/and silver nanoparticles (CuNPs or/and AgNPs). 24,29,32 Therefore, the ion exchange process between copper or/and silver cations and alkali cations to enhance the luminescence of Cr 3+ /RE 3+ co-doped has been studied in recent times.…”
Section: Introductionmentioning
confidence: 84%
“…3,12,19 In fact, the ion exchange process between coinage ions and alkali ions has many advantages compared with other traditional methods. 21 For example, in many previous researches 22–24 as well as in our recent work, 25 it was shown that the coinage ions introduced by the ion exchange processes could significantly affect the optical properties of the glasses such as the refractive index, the optical density, the near-infrared emission spectrum, or even chemically strengthen the glasses 26,27 as well as modify glass structure. 28 …”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Lanthanide-ion-doped glasses were considerably investigated as luminescent materials for different photonic and optoelectronic applications due to their high transparency in broad wavelengths and easy manufacturing techniques compared to crystals and powders. 22 Besides, low phonon energy is one of the most desirable properties expected from an UC host as it reduces nonradiative transition rates. 23 Hereupon, tellurite glasses possess one of the lowest phonon energies (600−850 cm −1 ) among all oxide glasses.…”
Section: Introductionmentioning
confidence: 99%